2009
DOI: 10.1111/j.1467-7687.2009.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Weighting of vowel cues explains patterns of word–object associative learning

Abstract: Previous research has demonstrated that infants under 17 months have difficulty learning novel words in the laboratory when the words differ by only one consonant sound, irrespective of the magnitude of that difference. The current study explored whether 15-month-old infants can learn novel words that differ in only one vowel sound. The rich acoustic/phonetic properties of vowels allow for a detailed analysis of the contribution of acoustic/phonetic cues to infants' performance with similar-sounding words. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 30 publications
7
122
2
Order By: Relevance
“…Floccia, Nazzi, Delle Luche, Poltrock, & Goslin, 2013;Mani & Plunkett, 2007). In the case of both vowels and consonants, sensitivity to mispronunciations appears to vary depending on the specific contrast used (Curtin, Fennell, & Escudero, 2009;Mani, Coleman, & Plunkett, 2008;, 2011Van der Feest, 2007;White & Morgan, 2008). Mispronunciation studies are not limited to infants and toddlers: in a study assessing mispronunciations in preschoolers, they demonstrate a transient phase of comparable sensitivity to vowel and consonant changes (Havy, Bertoncini, & Nazzi, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Floccia, Nazzi, Delle Luche, Poltrock, & Goslin, 2013;Mani & Plunkett, 2007). In the case of both vowels and consonants, sensitivity to mispronunciations appears to vary depending on the specific contrast used (Curtin, Fennell, & Escudero, 2009;Mani, Coleman, & Plunkett, 2008;, 2011Van der Feest, 2007;White & Morgan, 2008). Mispronunciation studies are not limited to infants and toddlers: in a study assessing mispronunciations in preschoolers, they demonstrate a transient phase of comparable sensitivity to vowel and consonant changes (Havy, Bertoncini, & Nazzi, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Several studies on English-learning infants showed that they are able to learn words differing only by one consonant feature as early as 14 months (Yoshida, Fennell, Swingley, & Werker, 2009) to 17 months of age (Werker, Fennell, Corcoran, & Stager, 2002). However, for vowels, infants sometimes succeeded by 14/15 months of age when the words differed by several features (Curtin, Fennell, & Escudero, 2009;Mani & Plunkett, 2008), but there is no evidence so far that they succeed with one-feature contrasts before 18 months of age (Dietrich, Swingley, & Werker, 2007). A similar asymmetry was found for French-speaking infants during the same age period using object manipulation tasks.…”
Section: Introductionmentioning
confidence: 98%
“…Clearly, a significant number of research results indicate that vowels are phonologically specified in the lexicon (Dietrich, Swingley, and Werker, 2007;Plunkett, 2007, 2010;Ramon-Casas et al, 2009;Swingley and Aslin, 2000). But, it is also true that certain acoustic dimensions may have an earlier representation than others (Curtin, Fennell and Escudero, 2009;Mani, Coleman and Plunkett, 2008), in the same way as the voicing dimension for consonants is possibly less well specified in the early lexicon (Mani and Plunkett, 2010;Van der Feest, 2007). However, the observation of a consonantal bias in certain tasks, but not in others, points to a different level of analysis, as it suggests differences in the use anales de psicología, 2014, vol.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, vowels need to differ in more than one dimension to observe a differential response in the child's attentional behavior . Changes in height dimension are detected earlier than changes in backness or roundness, from 15 months of age (Curtin et al, 2009).…”
Section: Phonological Representation In Learning New Wordsmentioning
confidence: 99%
See 1 more Smart Citation